Truck factors for flexible pavement design in Costa Rica: Historical analysis for the 2007-2017 period - Allen, Jaime (2025)
The truck factor is one of the main components in the estimation of the load demand that pavements will have. For this reason, having reliable truck factors is of utmost importance during the design stage. In the present study, the databases on truck factors calculated between 2007 and 2017 were compiled and analysed by LanammeUCR. More than 15 million heavy vehicles were analysed, distributed on different routes in the country. Given the need to have updated truck factors that take into account the national reality, both during the period without weight control and during the period with, truck factors are generated that are associated with a specific level of reliability and that consider the proportion of vehicles that contribute to their estimate.